Influence of body composition and muscle strength on outcomes after multimodal oesophageal cancer treatment. Issue 3 (25th February 2020) - Hagens, Eliza R.C.; Feenstra, Minke L.; van Egmond, Maarten A.; van Laarhoven, Hanneke W.M.; Hulshof, Maarten C.C.M.; Boshier, Piers R.; Low, Donald E.; van Berge Henegouwen, Mark I.; Gisbertz, Suzanne S.
Abstract: Background: Influence of sarcopenia in combination with other body composition parameters and muscle strength on outcomes after oesophageal surgery for oesophageal cancer remains unclear. The objectives were (i) to describe the incidence of sarcopenia in relation to adipose tissue quantity and distribution and muscle strength; (ii) to evaluate if neoadjuvant chemoradiation (nCRTx) influences body composition and muscle strength; and (iii) to evaluate the influence of body composition and muscle strength on post‐operative morbidity and long‐term survival. Methods: This retrospective study included patients with oesophageal cancer who received nCRTx followed by surgery between January 2011 and 2016. Skeletal muscle, visceral, and subcutaneous adipose tissue cross‐sectional areas were calculated based on computed tomography scans, and muscle strength was measured using hand grip tests, 30 seconds chair stand tests, and maximal inspiratory and expiratory pressure tests prior to nCRTx and after nCRTx. Results: A total of 322 patients were included in this study. Sarcopenia was present in 55.6% of the patients prior to nCRTx and in 58.2% after nCRTx ( P  = 0.082). Patients with sarcopenia had a significantly lower muscle strength and higher fat percentage. The muscle strength and incidence of sarcopenia increased while the mean body mass index and fat percentage decreased during nCRTx. A body mass index above 25 kg/m 2 was associated with anastomotic leakage ( P  = 0.032). Other body composition parameters were not associated with post‐operative morbidity. A lower handgrip strength prior to nCRTx was associated with pulmonary and cardiac complications ( P  = 0.023 and P  = 0.009, respectively). In multivariable analysis, a lower number of stands during the 30 seconds chair stand test prior to nCRTx (hazard ratio 0.93, 95% confidence interval 0.87–0.99, P  = 0.017) and visceral adipose tissue of >128 cm 2 after nCRTx (hazard ratio 1.81, 95% confidence interval 1.30–2.53, P  = 0.001) were associated with worse overall survival. Conclusions: Sarcopenia occurs frequently in patients with oesophageal cancer and is associated with less muscle strength and a higher fat percentage. Body composition changes during nCRTx did not influence survival. Impaired muscle strength and a high amount of visceral adipose tissue are associated with worse survival. Therefore, patients with poor fitness might benefit from preoperative nutritional and muscle strengthening guidance, aiming to increase muscle strength and decrease visceral adipose tissue. However, this should be confirmed in a large prospective study.